s*4-46=-2

Simple and best practice solution for s*4-46=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s*4-46=-2 equation:


Simplifying
s * 4 + -46 = -2

Reorder the terms for easier multiplication:
4s + -46 = -2

Reorder the terms:
-46 + 4s = -2

Solving
-46 + 4s = -2

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '46' to each side of the equation.
-46 + 46 + 4s = -2 + 46

Combine like terms: -46 + 46 = 0
0 + 4s = -2 + 46
4s = -2 + 46

Combine like terms: -2 + 46 = 44
4s = 44

Divide each side by '4'.
s = 11

Simplifying
s = 11

See similar equations:

| 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 | | -2(x+7)=14 | | 2A+2b=bc | | f(2n+1)=f(n)+f(n-1) | | 6x-6=-15 | | (q-9)*4=8 | | (9c+5)(7c-1)=0 | | -10m-11m+13m=16 | | p(x)=2x^3+x^2-49x+8 | | (q-4)*9=8 | | 6j(j+4)=0 | | x+x^2=8.5 |

Equations solver categories